Die rol van die openbare pers in die bevordering en totstandkoming van die kerkvereniging van 1885 - Pretorius, S. P. (Hervormde teologiese studies, 1987)
The contribution by the public press in promoting and establishing the merging of the three existing churches in the Zuid-Afrikaansche Republiek in the period 1881-1885 With this paper it is endeavoured to indicate that the public press, particularly in the years 1881 to 1885, made an important contribution to the promotion of the merging of the three existing churches in the Zuid-Afrikaansche Republiek in that same period. The hitherto unknown unity resulting from the developing Afrikaner Nationalism after the First Boer War of 1880 to 1881, has been overemphasized by the press to encourage a sense of emotionality to permit the political unity to overflow into the ecclesiastical province.